Effect of several types of endophytic fungi isolates Beauveria bassiana in suppressing seed-borne pathogens Colletotrichumspp - Dini Puspita , Yanty; Trizelia; Darnetty; Jumsu , Trisno (Jurnal Online Pertanian Tropik, 2021)
Anthracnose is one of the most important seed-borne diseases in chili plants because this disease can reduce the quantity and quality of chilies and cause substantial economic losses. The aim of this study was to obtain the best isolates from various types of endophytic fungi Beauveria bassiana in suppressing the growth of pathogens. chili seed borne disease caused by the fungus Colletotrichum spp. The design used in this study was a completely randomized design (CRD) consisting of 6 treatments. The treatments consisted of control and 5 types of B. bassiana isolates (PD114, TD312, WS, BbKo, KT2B23). Parameters observed in this study were chili seeds that were attacked by Colletotrichum spp., normal seed germination on paper-to-paper test, length of plumule and radicle. Results. The study showed that different types of B. bassiana isolates could reduce the attack rate of seed-borne pathogenic fungi Colletotrichum spp. KT2B23 isolate was the best isolate in suppressing chili seed-borne pathogens.